2019
DOI: 10.1107/s1600576719010707
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the strain relaxation processes in silicon nanowire arrays by X-ray diffraction

Abstract: Investigations performed on silicon nanowires of different lengths by scanning electron microscopy revealed coalescence processes in longer nanowires. Using X‐ray diffraction (XRD), it was found that the shape of the pole figure in reciprocal space is ellipsoidal. This is the signature of lattice defects generated by the relaxation of the strain concentrated in the coalescence regions. This observation is strengthened by the deviation of the XRD peaks from Gaussianity and the appearance of the acoustic phonon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…10 (a). Similarly, the pristine NWs exhibit higher strain 42 , and upon sintering, surface energy minimization stabilizes the lattice vibration and reduces stress and strain on the NWs array, as confirmed from Fig. 10 (b).…”
Section: Discussionmentioning
confidence: 59%
“…10 (a). Similarly, the pristine NWs exhibit higher strain 42 , and upon sintering, surface energy minimization stabilizes the lattice vibration and reduces stress and strain on the NWs array, as confirmed from Fig. 10 (b).…”
Section: Discussionmentioning
confidence: 59%
“…4(e) and 4( f)]. In contrast to Si nanowires, for which we showed that the bending and torsion phenomena govern the strain formation and the coalescence joints favor the strain relaxation processes (Romanitan et al, 2019), these measurements show no evidence of strain relaxation (i.e. relaxation degree is zero) in porous layers.…”
Section: Research Papersmentioning
confidence: 67%
“…This is possible by taking into account the small length of our arrays. Also, previous investigations in highly dense nanowire arrays prepared by MACE showed the occurrence of edge and screw threading dislocations only for wires longer than 9 µm [23]. At the same time, we must consider the previous findings from the rocking curves profiles, indicating a relationship between the array length and the XRDS intensity, which was attributed to the presence of the structural defects.…”
Section: A Structure and Pl Properties Of Silicon Nanowiresmentioning
confidence: 82%
“…These profiles were obtained in the framework of grazing-incidence X-ray diffraction on highlyasymmetric (111) reflection, which allowed us to attain different X-ray penetration depths, varying the incidence angles of the X-ray source. Further details regarding the grazingincidence X-ray diffraction technique on (111) in nanowires, as well as for the bending profiles can be found in [23].…”
Section: A Structure and Pl Properties Of Silicon Nanowiresmentioning
confidence: 99%